Le Langage Solitaire Chez L’enfant Trisomique - Chibani, Abdellatif; Badidi, Moulay Touhami (International Journal of Education, Culture, and Society, 2025)
Solitary language, defined as the verbal expression of a person in the absence of a direct interlocutor, is observed very frequently in children with trisomy 21, although it is not considered a pathological manifestation. This study aims to explore the role or functions of this verbal behavior. Semi-structured interviews were conducted with their parents. The results show that speaking alone fulfills several functions: cognitive, emotional, and social. Information collected from parents suggests that solitary language is an adaptive strategy contributing to the emotional regulation of children with trisomy 21.